First records of the American bullfrog Lithobates catesbeianus (Shaw, 1802) in Slovenia - Nino Kirbiš; Matjaž Bedjanič; Jana Kus Veenvliet; Paul Veenvliet; David Stanković; Gregor Lipovšek; Katja Poboljšaj (Natura Sloveniae)
The American bullfrog Lithobates catesbeianus is one of the 100 worst alien species in the world. It has been introduced to several European countries. During our field search activities in May 2014 and June 2015, a male bullfrog advertisement call was heard at Fiesa Lakes in Slovenia. On September 2015, a male specimen of the American bullfrog was caught in a funnel trap at the same location. These are the first records of the occurrence of this invasive species in Slovenia. Further studies should be conducted to evaluate if an actual population is present in the area. Eradication measures should commence immediately as chances for the establishment of naturalized bullfrog populations here are high.